Fiscal Policy and the Economic Restructuring of Economies in Transition - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1993)
This paper discusses major fiscal issues faced by the previously centrally planned economies in their transition to market economies. It focuses on three main topics: (a) the extent to which the budget deficit should be a guide to policy; (b) the reforms that must be carried out in tax legislation and tax administration; and (c) the required changes in public expenditure and in the setting up of institutions to manage public spending.